Training English Conference Interpreters Peculiarities at Higher Educational Establishments in Ukraine - Ageicheva, Anna; Hunchenko, Yuliia; Kalnik, Oleksandr; Koshlata, Alla (International Journal of Engineering and Technology, 2018)
The article describes topical problems of the present-day situation with conference interpretation in Ukraine (working conditions and the time pattern, difficulties caused by the imperfect organizing and management of conferences, inadequate equipment, and specific difficulties of simultaneous interpretation) and considers certain aspects of oral simultaneous translation training at higher educational establishments of Ukraine. The article also investigates developing interpreting skills at the examples of modern English economic terminology with regard to the main functions of compound noun economic terms in modern English scientific-economic texts. Special training exercises and techniques are suggested to be applied in the teaching process.Â Â Â